The impact of an active lifestyle on markers of intestinal inflammation in Parkinson’s disease: Preliminary findings - Nesrine Chtioui; Christian Duval; David H. St-Pierre (Clinical Parkinsonism & Related Disorders)
Alterations in the gut microbiota leading to intestinal inflammation and decreased levels of Short Chain Fatty Acids (SCFA) has been observed in Parkinson’s disease (PD). Objective: The aim of this study was to compare these factors between physically active and less active people with PD. Methods: Stool, plasma samples and clinical data were collected from 35 people with PD (20 men and 15 women, mean age 66 years). Their level of physical activity was retrospectively assessed using the International Physical Activity Questionnaire (IPAQ). Participants were divided into two groups based on their physical activity level: Active and Inactive. Both SCFA and calprotectin, a marker of intestinal inflammation, were respectively measured by GC–MS and ELISA, according to standardized, validated protocols. Results: Age, disease stage (Hoen & Yahr) and Montreal Cognitive Assessments (MoCA) were similar between groups. Acetate, propionate, and butyrate levels were significantly higher in the Active group than in the Inactive group. In addition, fecal calprotectin was significantly lower in the Active group than in the Inactive group. The constipation values were significantly lower in the Active group. Conclusion: Our results suggest that an active lifestyle with regular physical activity is beneficial in patients with PD, through increased production of SCFA by the gut microbiome, and reduced intestinal inflammation and constipation.